যদি \(x = \cfrac{1}{2-\sqrt3}\) হয়, তবে দেখাও যে, \(\cfrac{1}{x-2}+\cfrac{1}{x-\sqrt 3}=\cfrac{x}{2\sqrt3}\)
\(x = \cfrac{1}{2-\sqrt3}\)
\(=\cfrac{(2+\sqrt3)}{(2-\sqrt3)(2+\sqrt3)}\)
\(=\cfrac{2+\sqrt3}{4-3}=\cfrac{2+\sqrt3}{1}=2+\sqrt3\)
বামপক্ষ \(=\cfrac{1}{x-2}+\cfrac{1}{x-\sqrt 3}\)
\(=\cfrac{1}{\cancel2+\sqrt3-\cancel2}+\cfrac{1}{2+\cancel{\sqrt3}-\cancel{\sqrt 3}}\)
\(=\cfrac{1}{\sqrt3}+\cfrac{1}{2}\)
\(=\cfrac{2+\sqrt3}{2\sqrt3}\)
ডানপক্ষ \(=\cfrac{x}{2\sqrt3}\)
\(=\cfrac{2+\sqrt3}{2\sqrt3}\)
\(\therefore\) বামপক্ষ = ডানপক্ষ [প্রমানিত]